Evaluating second language courses - Griffee, Dale; Gorsuch, Greta (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
Typically, books on evaluation in the second and foreign language field deal with large programs and often result from large-scale studies done by the authors. The challenge for ordinary second and foreign language classroom teachers is that they must extrapolate techniques or strategies for evaluation from a very large scale to a much smaller scale, that of the course. At the same time, classroom teachers are responsible for outcomes of their courses and need to do evaluation on a scale and for needs of their choosing. Evaluating Second Language Courses is designed for classroom teachers who are dealing with a single course, and who wish to understand and improve some aspect of their course.